Optimizing the Use of the "ELSIMIL" Application in Preventing Stunting Through Pocket Book Media at the Balowerti Community Health Center, Kediri City - Krit Mahayuning Nusantarie; Hesti Restu Kartika; Yenny Puspitasari; Damaris Prastyawati; Lelyans Surya Rismasinapa; Wahyu Apriliani (Journal of Community Engagement in Health, 2024)
Stunting is a major problem for babies and children under two years of age. Therefore, this condition must be addressed immediately because it can hinder the momentum of Indonesia's Golden Generation in 2045. To realize the Stunting Reduction Acceleration Program from the upstream, the BKKBN launched the "ELSIMIL" (Electronic Ready for Marriage and Pregnancy) application. A useful application to find out in advance the prospective bride and groom's preparations for the potential baby to be born by looking at the health condition of the prospective bride and groom. The aim is to increase (optimize) the use of the "ELSIMIL" application in preventing stunting through pocket book media at the Balowerti Health Center, Kediri City. The data collection technique uses observational techniques and the instrument used is a questionnaire. Then analyze the problem using SWOT and Fishbone. Based on the results of residency activities in the working area of the Balowerti Community Health Center, there are still toddlers with stunting found in the 2023 projection starting from January-March 2023, namely 118 toddlers from 5 sub-districts accompanied by the lack of optimal use of the "ELSIMIL" application in the working area of the Balowerti Community Health Center, Kediri City. So it can be concluded that the use of the "ELSIMIL" application is still not optimal in preventing stunting. The proposed use of pocket book media is one strategy that aims to increase the knowledge and understanding of mothers and their families in preventing stunting from an early age.